The long boom and the early bust: the Portuguese economy in the era of financialisation - Mamede, R. P. (2018)
The notion of ‘financialisation’ broadly refers to the growing weight of finance in contemporary economies. Taking this into account, this chapter focuses on the long-run macroeconomic development and recent financial and economic crisis of the Portuguese economy. Contrary to Greece, Ireland, and Spain, the dismal performance of the Portuguese economy is not solely a post-subprime crisis phenomenon. The sharp discontinuity in GDP growth around the turn of the century is a distinctive feature of Portugal in the EU context and, although several factors account for this discontinuity, the process of financialisation of the Portuguese economy is an essential part of the explanation. This process in Portugal was essentially characterised by a large increase in bank credit to the private sector, resulting from a combination of demand- and supply-side factors that produced a wide availability of credit at historically low interest rates. Thus, we suggest that the Portuguese experience can be labelled a ‘debt-led domestic demand growth’ model. However, after 2000 the Portuguese economy experienced a succession of shocks, and an exhaustion of the domestic debt-led growth at a much earlier stage than other countries, resulting in a sharp economic slowdown, with negative consequences for public finances. The high levels of public and private indebtedness were a decisive factor behind the steep rise in the Portuguese sovereign bonds interest rates between 2010 and 2012. Finally, we assess the impact of financialisation in the current account, investment, consumption, and inequality; articulating these domains with the general growth model. Our conclusion is that the increase in the importance of finance ended having a clear negative impact on the three former domains, while the negative impact on income inequality was less pronounced.